2013
DOI: 10.1177/0888406413478637
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Coaching on Teachers’ Use of Function-Based Interventions for Students With Severe Disabilities

Abstract: The purpose of this study was to evaluate the effects of coaching on special education teachers' implementation of function-based interventions with students with severe disabilities through the use of a delayed multiple baseline across participants design. This study also sought to examine if teachers could generalize the ability to implement function-based interventions to different situations with their students.Additionally, this study examined the effect of the function-based intervention on the students'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…Although the teachers' baseline data were not always consistent, all teachers met their OTR goal on each intervention session. The findings of this study are consistent with previous research, indicating that PD and teacher coaching can have an immediate effect on the implementation of evidence-based strategies (Bethune & Wood, 2013;Kretlow et al, 2012;Simonson et al, 2010;Sutherland et al, 2000). Like other successful studies, this study used PD and teacher coaching as a package; therefore, these positive results were not surprising.…”
Section: Teacher Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Although the teachers' baseline data were not always consistent, all teachers met their OTR goal on each intervention session. The findings of this study are consistent with previous research, indicating that PD and teacher coaching can have an immediate effect on the implementation of evidence-based strategies (Bethune & Wood, 2013;Kretlow et al, 2012;Simonson et al, 2010;Sutherland et al, 2000). Like other successful studies, this study used PD and teacher coaching as a package; therefore, these positive results were not surprising.…”
Section: Teacher Resultssupporting
confidence: 82%
“…Maintenance data and responses to the social validity surveys suggest that teachers felt like this was a worthwhile intervention and would continue to use it without coaching. Similar studies that collected maintenance data 5-7 days after the conclusion of intervention have shown that teachers maintain evidence-based strategies at goal levels after coaching ended (Bethune & Wood, 2013;Codding et al, 2005;Duchaine et al, 2011). Other researchers have shown positive maintenance results as far as three months after the intervention (Miller et al, 1991;Thompson, Marchant, Anderson, Prater, & Gibb, 2012).…”
Section: Teacher Resultsmentioning
confidence: 98%
“…There is an extensive body of literature on promoting fidelity of implementation through effective coaching techniques. Side-by-side coaching, for example, has been used to ensure the fidelity with which individual behavior support plans are implemented in early childhood programs (e.g., Bethune & Wood, 2013) and the fidelity with which teachers implement class-wide positive behavior support strategies in early childhood settings (e.g., Stormont et al, 2015). Researchers have also examined the utility of behavioral consultation models on the implementation of individualized behavior support plans (e.g., Noell & Gansle, 2014); the plan implementation phase of behavioral consultation shares characteristics with common coaching models including observation, monitoring implementation, supporting plan revisions, and providing additional training as needed (Sheridan et al, 2013).…”
Section: Preparing Behavior Analystsmentioning
confidence: 99%
“…Typical professional development or learning activities take on many different forms, from workshops (e.g., Courtade, Browder, Spooner, & DiBiase, 2010) to online modules and courses (e.g., Hanline, Hatoum, & Riggie, 2013) to coaching (e.g., Bethune & Wood, 2013). In today's era of educational reform (e.g., increased emphassis on teacher evaluations; Sledge & Pazey, 2013), professional learning should also include occasions for teachers to reflect critically on their practice and to fashion new knowledge and beliefs about content, pedagogy, and learners (Avalos, 2011;Prawat, 1992).…”
Section: Professional Development and Learningmentioning
confidence: 99%